2015
DOI: 10.1186/s13024-015-0046-3
|View full text |Cite|
|
Sign up to set email alerts
|

Ethosuximide ameliorates neurodegenerative disease phenotypes by modulating DAF-16/FOXO target gene expression

Abstract: BackgroundMany neurodegenerative diseases are associated with protein misfolding/aggregation. Treatments mitigating the effects of such common pathological processes, rather than disease-specific symptoms, therefore have general therapeutic potential.ResultsHere we report that the anti-epileptic drug ethosuximide rescues the short lifespan and chemosensory defects exhibited by C. elegans null mutants of dnj-14, the worm orthologue of the DNAJC5 gene mutated in autosomal-dominant adult-onset neuronal ceroid lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 55 publications
3
31
1
Order By: Relevance
“…These effects were attributed to the inhibition of dopamine 2-like receptor-mediated signaling, as elimination of the dopamine 2-like receptor in Tau V337M worms produces similar neuroprotective effects (104). In a recent study, the antiepileptic drug ethosuximide increased the lifespan and partially corrected the Unc phenotype in Tau V337M worms with the effect dependent on the insulinsignaling pathway (106).…”
Section: Drug Screening Using Tauopathy Models Of C Elegansmentioning
confidence: 99%
“…These effects were attributed to the inhibition of dopamine 2-like receptor-mediated signaling, as elimination of the dopamine 2-like receptor in Tau V337M worms produces similar neuroprotective effects (104). In a recent study, the antiepileptic drug ethosuximide increased the lifespan and partially corrected the Unc phenotype in Tau V337M worms with the effect dependent on the insulinsignaling pathway (106).…”
Section: Drug Screening Using Tauopathy Models Of C Elegansmentioning
confidence: 99%
“…Azaperone, in particular, effectively ameliorated mutant Tau-induced functional defects and reduced the level of insoluble Tau aggregation [ 37 ]. Finally, a recent study reported that the anti-epileptic drug, ethosuximide, could ameliorate the impaired motility and reduced lifespan phenotypes of the Tau V337 M worm FTDP-17 model [ 38 ]. Interestingly, ethosuximide’s action in this worm Tau model was independent of its main proposed target in epilepsy, the T-type calcium channel.…”
Section: Reviewmentioning
confidence: 99%
“…HIL-7 (Histone H1 Like) gene expression may be associated with Ethosuximide treatment, a drug that increases worm lifespan and affects DAF-16/FOXO target gene expression (X. Chen et al, 2015). TTH-1 (Thymosin beta) is significantly increased in daf-2 mutants, which are very long-lived, suggesting possible pro-longevity status by association (Narayan et al, 2016).…”
Section: Predicted Pro-longevity Worm Genesmentioning
confidence: 99%